Inovasi Kesehatan Keluarga : Analisis Program ‘Bapakku Hebat’ sebagai Strategi Puskesmas Omben dalam Pencegahan Stunting - Enggar Enggar; Zainal Fatah; Kristyan Dwijosusilo; Ika Devy Pramudiana (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Stunting remains a significant health problem in rural areas, particularly due to the lack of father involvement in child care. The “Bapakku Hebat” program initiated by the Omben Health Center emerged as a breakthrough to strengthen the role of fathers in stunting prevention efforts through family health posts. This study adopted a qualitative descriptive approach to investigate the implementation, effects, and barriers of the program. The research findings indicated an increase in father involvement in health post activities, nutrition counseling, and child health monitoring. The program successfully reduced the prevalence of stunting risk by 10% in a year by increasing health post coverage and changing family behavior in providing nutrition. Key driving factors included inter-sectoral collaboration with village governments, health cadres, and farming communities that strengthened social networks and local resources. However, challenges remain, such as budget constraints, a lack of male cadres, and the influence of cultural norms that consider childcare as a woman’s responsibility. The “Bapakku Hebat” program shows that active father involvement can increase family awareness of the importance of fulfilling children’s nutrition. These findings emphasize the importance of gender-sensitive family health policies and cross-sectoral support to ensure the sustainability of the program. This research is expected to be a reference for other regions in implementing similar innovations to reduce the prevalence of stunting and improve the quality of child care. Furthermore, the success of the